(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The green economy is an economic development model that prioritizes sustainability, equity, and environmental preservation. This article explores the foundational principles of the green economy, its benefits and challenges, and examines global initiatives and case studies that illustrate its implementation. By analyzing various aspects of the green economy, the article aims to provide a comprehensive understanding of its potential to drive sustainable development and address pressing environmental issues.